Optimalisasi Kepatuhan Perawatan Mandiri Pasien Hipertensi Melalui Edukasi Discharge Planning Berbasis Media Visual - Niken Sri Wahyuni; Rahmania Ambarika (Yayasan Inspirasi El Burhani, 2026)
Introduction: Hypertension remains one of the leading non-communicable diseases worldwide and is a major contributor to cardiovascular morbidity and mortality. Poor adherence to self-care behaviors after hospital discharge, including medication compliance, dietary management, physical activity, and regular blood pressure monitoring, may increase the risk of complications and hospital readmissions. Effective discharge planning supported by visual educational media is needed to improve patients’ understanding and adherence to self-care practices. Objective: The purpose of this service was to improve self-care adherence among hypertensive patients through visual media-based discharge planning education at Al-Aziz Hospital Jombang. Method: This public service was conducted by implementing health education activities for hypertensive patients and their family caregivers using an educational and participatory approach. The intervention included interactive lectures, discussions, question-and-answer sessions, and the distribution of visual educational materials covering medication adherence, hypertension diet management, physical activity, blood pressure monitoring, follow-up care, and complication prevention. Result: The implementation of the visual media-based discharge planning education program involved 60 participants, consisting of 30 hypertensive patients and 30 family members. The evaluation results demonstrated an improvement in participants’ knowledge regarding hypertension management and self-care practices. The mean knowledge score increased from 16 before the intervention to 29 after the intervention, representing an 81.25% improvement in knowledge scores. The improvement was observed in several aspects of hypertension self-management, including medication adherence, dietary modification, regular physical activity, blood pressure monitoring, and early recognition of complications. Visual educational media facilitated information retention, enhanced participant engagement, and strengthened communication between healthcare providers, patients, and families during the discharge planning process. Conclusion: Visual media-based discharge planning education is an effective strategy for improving knowledge and supporting self-care adherence among hypertensive patients after hospital discharge. The program can contribute to better hypertension control, prevention of complications, and improvement of patients’ quality of life. Continuous implementation of structured discharge planning is recommended to strengthen long-term disease management